A Combined Approach of Identity Based and Attribute Based Encryption Service to Secure Data Processing in WBAN - Manish Shrivastava (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Wireless Body Area Network (WBAN) is a collection of wireless sensor nodes that can be placed inside or outside the body of a human or living person to observe or monitor the functionality and adjacent situations of the body. By using a wireless body network, the patient becomes more physically versatile and is no longer forced to stay in the hospitals. Cloud computing is the next big thing after the Internet in WBAN. Even though cloud is becoming more popular, ease of use and respectability, privacy issues and other security issues is a big setback in the field of cloud computing. Privacy and security are the key factors for cloud storage. Encryption is a prominent technology for protecting sensitive data. In this paper, a combined approach of identity-based and attribute-based access policy for encryption (CAIBABE) of cloud storage is proposed, which can be implemented on a cloud platform. In this work, the feasibility of the encryption algorithm for data security and privacy in cloud storage is analyzed in comparison with other existing algorithms.